ANALYSIS OF EFFECT OF ORGANIZATIONAL CULTURE, WORK DISCIPLINE AND COMMITMENT ORGANIZATION, THE PERFORMANCE OF HEALTH SALIDO PARAMEDICS PAINAN - Yulihardi, Yulihardi (Eko dan Bisnis: Riau Economic and Business Review, 2017)
The problem is analyzed in this study is "Energy Performance Paramedics The variables of this research is the influence of organizational culture, Discipline Work and Organizational Commitment (as independent variables) and the Energy Performance Paramedic (as dependent variable). This study of the level of performance Paramedical Personnel and Organizational Culture is also worth noting, Work Discipline and the Organizational Commitment. By working on improving performance Paramedical. Personnel Agencies to our goals, especially against Salido Painan health center.This study aims to reveal, Influence of Organizational Culture, Discipline Work and Organizational Commitment together on the Performance of Power Paramedical Health Center Painan Salido. Influence of Organizational Culture, Discipline Work and Organizational Commitment partially on Energy Performance Puskesmas paramedics Salido Painan with regression equation Y = 17,866+ 0,188X1 + 0,136X2 + 0,280X3. The conclusion that the hypothesis of partial and simultaneous variable Organizational Culture, Work and Organizational Commitment Discipline shown to have positive and significant impact on the performance of Puskesmas Paramedical Personnel Salido Painan by contributing 61.0% to the commitment of the Organization as the most dominant variable. Suggestion To be more focus on improving work discipline variable by taking into account the indicators